ANALISIS TINGKAT KERENTANAN PESISIR PANTAI SAGO SALIDO TERHADAP ABRASI DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Sari, Serli Mardilla (JURNAL BUANA, 2026)
The type of research used is descriptive quantitative. The objectives of this research are (1) To find out the physical characteristics (geomorphology, average tides, wave height, changes in coastline, beach slope, sea level rise and land use) at Sago Salido Beach, IV Jurai District, Pesisir Selatan Regency. (2) Find out the level of vulnerability of the coast of Sago Salido Beach to abrasion in IV Jurai District, Pesisir Selatan Regency. Measuring the level of coastal vulnerability in this study uses a weighting and scoring method based on the CVI (Coastal Vulnerability Index) parameter. The parameters used to determine coastal vulnerability are physical parameters and oceanographic parameters that are appropriate to coastal areas. The population in this study is along the Sago Salido coastline and sampling was carried out using a purposive sampling technique, which is based on changes in the coastline. This research found 3 levels of coastal vulnerability to abrasion, namely a high level of vulnerability of 24% in the northern part of Kp. Sago Reef. The level of moderate vulnerability is 9% (5% in the central part of Kp. Karang Sago and 4% in the northern part of Kp. Karang Sago) and the level of low vulnerability is 67% (27% in the central part of Kp. Karang Sago and 40% in the southern part Kp. Karang Sago).